The Challenges of Inclusive Education in Indonesia - Suhendri (Kusuma Negara Business School, 2020)
Inclusive education is the fulfillment of the right to education for all people, including children with special needs. In Indonesia, the right to education of children with special needs is guaranteed and protected by the constitution. This paper aims to discuss the challenges of inclusive education in Indonesia. This paper finds that the challenges of inclusive education in Indonesia are socio-cultural issues that include the belief system of society and parents; regulatory issues, technical policies, and operations of inclusive education; as well as a support system. Based on these findings, it is hoped that all stakeholders will have a commitment to accept the presence of children with special needs, conduct socialization, and accelerate regulations on inclusive education in the regions.